Pengaruh Kepemilikan Institusional, Ukuran Perusahaan, dan Leverage terhadap Kinerja Keuangan Perusahaan Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia - Muttaqien, Zainun; Damayanti, Damayanti (STIE PENA, 2022)
This research aims to prove the influence of Institutional Ownership, Company Size and Leverage on the Financial Performance of Food and Beverage Companies listed on the Indonesia Stock Exchange. The sample in this study amounted to 7 food and beverage companies listed on the Indonesia Stock Exchange for the period 2016 to 2020. The sample determination in this study was conducted using purposive sampling, which is a sampling technique using certain criteria, which obtained a sample of 7 food and beverage companies for 5 years to obtain 35 observations. The data analysis technique used multiple linear regression analysis. Based on the results of the study, it shows that institutional ownership variable has a significant negative effect on the company's financial performance (ROA), the company size variable has an insignificant negative effect on the company's financial performance (ROA), the leverage variable has a significant negative effect on the company's financial performance (ROA). The results of the determination test show that the variables of institutional ownership, firm size and leverage are able to explain the variable of the company's financial performance by 46.4% while 53.6% is explained by other factors that are not included in the research model carried out.Keywords: Company Size; Institutional Ownership; Leverage